Documents from the history of economic thought - Samuels, Warren J., 1933- (Research in the history of economic thought and methodology ;, 2007)
Volume 25-B of this title continues the multiple series of class notes with Glenn Johnson's notes from Charles M. Hardin's 1947 course on the politics of agriculture and with Warren Samuels' notes from Charlton Tebeau's 1953 course on United States constitutional history. The major item consists of Allan Schmid's journal entries distributed in connection with his courses on institutional and behavioral economics. The series presents review essays, multiple reviews and mini symposia on new-works in this field. The volumes are broad in scope and fill a substantial gap in this field.